The English influence on the Japanese Language - Safina Farida Axatovna (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
This article provides a comprehensive review of research on the Anglicization of the Japanese lexicon, tracing its development from the mid-19th century to the present day, when Japan reopened its doors to Western countries. It examines the characteristics of Anglicisms in Japanese, utilizing a typology of lexical borrowings proposed by Pulcini, which categorizes them into loanwords, Anglicisms, semantic loans. Additionally, the article suggests potential avenues for future qualitative and quantitative comparative analysis to deepen our understanding of Anglicisms in Japanese and their implications for global business language.